Crocin supplementation during oocyte maturation enhances antioxidant defence and subsequent cleavage rate. Issue 2 (10th December 2018) - Chen, Xuan; Xuan, Biao; Xu, Da; Wang, Qiuyue; Cheng, Mimi; Jin, Yi
Contents: The purpose of the present study was to assess the effect of crocin supplementation during oocyte maturation on the antioxidant defence and anti‐apoptotic ability and subsequent developmental competence of porcine oocytes. Oocytes were cultured in media containing 0, 300, 400 or 500 µg/ml of crocin. Upon maturation, the maturation rates, reactive oxygen species (ROS) and glutathione (GSH) levels, mRNA expression of genes ( SOD, CAT, GPx, Bcl‐2, BAX and Caspase3 ), expression of cleaved caspase3 and subsequent embryo cleavage rates were measured. Results indicated that the maturation rate of the 400 µg/ml group was 86.80% ( p < 0.01). The ROS concentration of the 500 µg/ml group was the lowest ( p < 0.01). The GSH concentration of the 400 µg/ml group was the highest ( p < 0.01). The SOD, CAT and GPx mRNA expression levels were the highest in the 300, 400 and 500 µg/ml groups, respectively, with the expression levels of all genes being significantly higher than that of the control group ( p < 0.01). The Bcl‐2/BAX mRNA expression ratio in 400 and 500 µg/ml groups significantly higher than other groups and significantly decreased caspase3 expression level ( p < 0.01). The expression level of cleaved caspase3 in the 500 µg/ml treatment group was the lowest, significantly lower than that of the control group ( p < 0.01). The cleavage rate of the 400 µg/ml group was 62.50% ( p < 0.01). These experimental results show that the supplementation of in vitro culture medium with 400 µg/ml of crocin significantly enhanced the antioxidant defence and anti‐apoptotic ability and subsequent cleavage rate of porcine embryo.